2022
DOI: 10.3390/ijerph19137783
|View full text |Cite
|
Sign up to set email alerts
|

The Detection of SARS-CoV2 Antigen in Wastewater Using an Automated Chemiluminescence Enzyme Immunoassay

Abstract: The SARS-CoV-2 virus, which is driving the current COVID-19 epidemic, has been detected in wastewater and is being utilized as a surveillance tool to establish an early warning system to aid in the management and prevention of future pandemics. qPCR is the method usually used to detect SARS-CoV-2 in wastewater. There has been no study using an immunoassay that is less laboratory-intensive than qPCR with a shorter turnaround time. Therefore, we aimed to evaluate the performance of an automated chemiluminescence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…We previously reported that RT-qPCR [22] and CLEIA [6] could be used to detect SARS-CoV-2 in wastewater. In the present study, we determined the presence of SARS-CoV-2 in hospital wastewater samples using RT-qPCR to identify SAR-CoV-2 viral RNA and CLEIA to identify SAR-CoV-2 viral antigen.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously reported that RT-qPCR [22] and CLEIA [6] could be used to detect SARS-CoV-2 in wastewater. In the present study, we determined the presence of SARS-CoV-2 in hospital wastewater samples using RT-qPCR to identify SAR-CoV-2 viral RNA and CLEIA to identify SAR-CoV-2 viral antigen.…”
Section: Discussionmentioning
confidence: 99%
“…CLEIA is widely used for COVID-19 screening in Japanese airports, and it has been used for community and population screening to identify SARS-CoV-2 nucleocapsid protein in specimens (nasopharyngeal swabs) [27]. Furthermore, we established the potential role of CLEIA for identifying SARS-CoV-2 antigen in fresh market wastewater [6].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Immunoassay systems have been widely used as a biotechnology tool for detection of SARS-CoV-2 RNA 10,11 and viral proteins. 12 However, human antibodies shed in urine and feces have not been targeted as a biomarker in wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…Samples for immunoassays are typically collected from serum 17 , but there have also been recent advances in use of immunosensors targeting the viral antigen protein in wastewater. 18,19 Human antibodies shed in urine and feces have not been targeted as an immune biomarker in wastewater, despite three years of intense focus on monitoring and mitigation of COVID-19 infections. Antibody measurements from fecal samples have already been highlighted as a non-invasive means to rapidly monitor the immune status of wildlife 20 Similarly, measurements from fecal samples are increasingly being used for studying various aspects of human health, 21,22 as fecal antibody levels are correlated with antibody levels in serum 23 , and have been demonstrated as a potential biomarker for detection of viral 24 and parasitic infections 25 in human urine samples.…”
mentioning
confidence: 99%